TI_GERICHTE 80.2021.119 vom 21. April 2021 , Procedura: ricorso, ricevibilità, firma manoscritta originale, termine per sanatoria - TI Tribunale d'appello (2021)
Procedura: ricorso, ricevibilità, firma manoscritta originale, termine per sanatoria